Pengaruh Kualitas Produk, Citra Merek, Harga dan Iklan Terhadap Keputusan Pembelian Sepeda Motor Honda Revo (Studi Kasus pada Konsumen Sepeda Motor Honda Revo Astra Motor Kebumen) - Aji Normawan Rosyid; Handoyo Djoko Waluyo; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed to determine the effect of product quality, brand image, product price and advertising on purchase decisions of Honda Revo motorcycle on consumer Astra Motor Kebumen and type of research used for this research is explanatory. Population is not limited to any consumer that Honda Revo motorcycle purchaser at Astra Motor Kebumen, as the Slovin’s theory,  sample set only by 86 people with spreading use of Non-Probability Sampling methods (insidental sampling). Data were analyzed using the coefficient of determination test, simple and multiple linear regression, cross tables and tests of significance with SPSS 18.0. The results showed that the product quality influence purchase decisions of 7.1 percent. Variables affect the brand image on purchasing decisions by 6 percent. Variable rates affect purchase decisions by 12.8 percent. Advertising influence the purchasing decisions of by 19.2 percent. Simultaneously, product quality, brand image, product price, and advertising affect purchasing decisions at 34.6 percent. The conclusion is the product quality, brand image, price, and advertising have positively and significant impact on purchasing decisions at Honda Revo motorcycle as evidenced from the results of the test f count (10.699) > f table (3.1079). If four factors are synergically balanced, the product will get a high level of consumer purchases will positively impact  in company sustainability.